Identification of exosomal muscle-specific miRNAs in serum of myotonic dystrophy patients relating to muscle disease progress. (16th June 2017) - Koutsoulidou, Andrie; Photiades, Marinos; Kyriakides, Tassos C.; Georgiou, Kristia; Prokopi, Marianna; Kapnisis, Konstantinos; Łusakowska, Anna; Nearchou, Marianna; Christou, Yiolanda; Papadimas, George K.; Anayiotos, Andreas; Kyriakou, Kyriakos; et al.
Abstract: Myotonic dystrophy type 1 (DM1) is the most common form of adult-onset muscular dystrophy, which is characterised by progressive muscle wasting and the discovery of reliable blood-based biomarkers could be useful for the disease progress monitoring. There have been some reports showing that the presence of specific miRNAs in blood correlates with DM1. In one of these, our group identified four muscle-specific miRNAs, miR-1, miR-133a, miR-133b and miR-206, which correlated with the progression of muscle wasting observed in DM1 patients. The levels of the four muscle-specific miRNAs were elevated in the serum of DM1 patients compared to healthy participants and were also elevated in the serum of progressive muscle wasting DM1 patients compared to disease-stable DM1 patients. The aim of this work was to characterise the ontology of these four muscle-specific miRNAs in the blood circulation of DM1 patients. Here we show that the four muscle-specific miRNAs are encapsulated within exosomes isolated from DM1 patients. Our results show for the first time, the presence of miRNAs encapsulated within exosomes in blood circulation of DM1 patients. More interestingly, the levels of the four exosomal muscle-specific miRNAs are associated with the progression of muscle wasting in DM1 patients. We propose that exosomal muscle-specific miRNAs may be useful molecular biomarkers for monitoring the progress of muscle wasting in DM1 patients. There has been a growing interest regarding the clinical applications of exosomes and their role in prognosis and therapy of various diseases and the above results contribute towards this way.